Evaluation of the pediatric airway: a review - Swain, Santosh Kumar (International Journal of Contemporary Pediatrics, 2022)
The airway in the pediatric age group is a complex structure that extends from the external nares to the junction of the larynx and trachea. The airway of pediatric patients has significant anatomical and physiological differences compared to the adult age group. The difficult airway in children is an important contributor to both morbidity and mortality of the patient. The symptoms and signs of pediatric patients with respiratory distress depend on the site and severity of the obstruction. It is essential to evaluate and localize the site and etiology of the obstruction of the pediatric airway. Pediatric otolaryngologists and anesthetists must have a strategy for managing the predicted difficult pediatric airway. Flexible nasopharyngolaryngoscopy is the gold standard method for predicting or knowing the difficult airway in children. The majority of pediatric patients who have difficult airways are identified preoperatively. Knowledge of the airway differences between the pediatric and adult ages will help clinicians anticipate and troubleshoot difficulties that may happen. This review article aims to discuss the evaluation of the pediatric airway including its anatomy and physiology of the airway, proper history taking, clinical examination, and investigations.